Quality Assurance In The Management Of Nigeria University Education - Joy C., Nzokurum; Agala, Humphrey O. (Advances in Social Sciences Research Journal, 2019)
This paper examined quality assurance in the management of Nigeria university education. It gave a background of the current situation of Nigeria university education and its need for quality assurance. The paper also revealed the several challenges facing quality assurance in the university education. The study adopted a descriptive survey design with population comprising all the lecturers in two public universities in Rivers State (i.e. University of Port Harcourt and Rivers State University). The researcher employed random sampling technique to draw respondents (lecturers) for the study. Two research questions were answered. The research instrument for this study was titled: Quality Assurance in the Management of University Education Questionnaire’ (QAMUEQ). The reliability of the instrument was established through the Cronbach alpha method; which produced a reliability coefficient of 0.74. The data obtained was analyzed using mean and standard deviation. The findings of the study showed that the respondents (i.e. lecturers) agreed to the fact that challenges of quality assurance in the management of Nigeria university education includes: Inadequate funding, frequent labour disputes and closures of universities, lack of information communication technology facilities, poor policy implementation, inadequate/poor quality of teaching staff, poor leadership and brain drain.; respondents aslo agreed that the strategies for quality assurance in management of Nigeria university education include effective records management system, instructional supervision, facility inspection, monitoring, staff quality control, implementation of minimum academic standard, students support and mentoring services, equitable disbursement of funds, etc. Among others, it was recommended that effective supervision of activities within the tertiary institutions should be enforced in order to attain quality assurance in tertiary institutions.